Sesame Oil Addition to Bamboo Reinforced Composite Matrix - Januar Putra Umba Kusairiawan; Akhmad Basuki Widodo; Dwisetiono Dwisetiono; Mochamad Arief Sofijanto (International Journal of Marine Engineering Innovation and Research, 2023)
Wooden ships use jati wood. Over time jati wood has become scarce. So that jati wood is relatively expensive. therefore bamboo is researched starting from the skin, bamboo meat, and bamboo internodes contained in the plant. In the structure of bamboo there are internodes. The bamboo segment is the weakness of the bamboo structure. The effect of bamboo segments in composite construction was investigated. Sesame oil replaces mineral oil and chemicals, because sesame oil is biodegradable, non-toxic, environmentally friendly, and renewable. To determine the effect of bamboo segments, tensile and bending tests will be conducted on the bamboo composite. The results of this research are expected to find alternative materials, namely bamboo fibre-based composites or so-called bamboo reinforcement plastics (BRP) as materials for making people's ships. This study found that the more layers of bamboo and bamboo segments are very influential in influencing the tensile and bending strength of a laminated material. The tensile testing value of layer 3 with segments reached 127.556 Mpa and without segments 933.333 as well as bending testing layer 3 with segments reached 113.889 Mpa and without segments 111.111 Mpa. From this value, the value has not met the standard of the Indonesian Classification Bureau (BKI).